Effect of Green Betel Leaf (Piper Betle) Decoction on Pathological Vaginal Discharge in Female Students of Cendrawasih Polytechnic Palu - Lestari, Novita; Abd. Rahman; Fauzan, Fauzan; Nur, Rosmala; Ni Wayan Sridani (Rifa'Institute, 2025)
Introduction: Pathological leucorrhea that is not properly treated can cause vaginitis, spread to the urinary tract, and lead to urinary tract infections with serious complications. Objective: To examine the effect of green betel leaf (Piper betle leaf) decoction on reducing the intensity of pathological leucorrhea among female students at Politeknik Cendrawasih Palu. Methods: This quantitative study applied a quasi-experimental design with a control group and pre-test post-test approach, involving 60 participants at Politeknik Cendrawasih Palu. Results and Discussion: Pre-test results showed that 61.7% of respondents were in the mild category and 18.3% in the severe category. Post-test findings indicated an increase in the normal category in the intervention group (30.0%). Wilcoxon Signed Ranks test revealed no significant change in the control group (p-value 0.1 > 0.05), while a significant effect was observed in the intervention group (p-value < 0.001), confirming the effectiveness of green betel leaf decoction. Conclusion: Green betel leaf decoction effectively reduces the intensity of pathological leucorrhea among female students